Ataques anfibios en culebras semiacuaticas: manejo del problema de la refracción por parte de especialistas y generalistas - Guillén, Fedro Carlos; Drummond Durey, Hugh (Instituto de Ecología, A.C., 1989)
We tested the hypothesis that aquatically specialised snakes posses finer correction mechanisms than terrestrial-aquatic generalists for air-to-water attacks involving a problem of light refraction. Five species of colubrid ankes were compared: two aquatic specialists (Thamnophis melanogaster and T. couchi) and two terrestrial-aquatic generalists (T. elegans and T. sistalis), as well as a water snake, Nerodia sipedon, belonging to a genus closely related to Thamnophis. Attacks were videorecorded in a experimental tank and transferred through a monitor to drawings for analysis. Attack speed and angular deviation target were measured. Since the image is always located above the actual position of the fish, an attack (should probably) be directed below the image in order to be successful. The aquatic specialists T. melanogaster and T couchi attacked significantly more often using trajectories below the image than the generalist, suggesting a mechanism compesating for refraction. On average, T. melanogaster made the fastest attacks.